Мисленнєво-мовленнєвий компонент творчого саморозвитку майбутніх лікарів - Слухенська, Руслана; Анжела, Angela, Медвідь, Medvid'; Первухіна, Світлана (Збірник наукових праць "Педагогіка формування творчої особистості у вищій і загальноосвітній школах" Запоріжжя : КПУ, 2019)
Гармонійне поєднання гуманітарної підготовки майбутніх фахівців з їхнім професійним становленням є однією з проблем медичної освіти. Концептуальні засади розвитку педагогічної освіти України формують зміст соціально-гуманітарної підготовки в інтенсифікації та професіоналізації мовної, філософської, політологічної, культурологічної, соціологічної, фізичної культури та санаторного виховання тощо; творчий потенціал майбутнього лікаря шляхом впровадження нестандартних методів навчальної діяльності, організації пошукової та дослідницької діяльності, просування ініціативи пошуку власних цілей тощо. Мета статті – охарактеризувати мисленнєво-мовленнєву складову частину творчого потенціалу майбутніх лікарів і визначити критерії, показники та рівні її формування. Необхідно звернути увагу на розширення медичного світогляду, формування професійної свідомості майбутніх лікарів, на зміцнення спрямованості на саморозвиток особистості студентів, що сприяє їх самореалізаціїта професійного самовизначення у підготовці фахівців (включаючи майбутніх лікарів). Професійна підготовка майбутніх лікарів – це безперервний процес їх формування не тільки як фахівців, а й як особистості. У статті розглядаються проблеми формування клінічного мислення як основи компетентнісно орієнтованих навичок і здібностей майбутніх лікарів, які можуть бути вирішені за допомогою інноваційних освітніх технологій, що забезпечують застосування методів формування творчого і системного мислення, створених не тільки відтворювати отримані завдання, але здобувати нестандартні навички. Перспективи подальших досліджень вбачаємо у розробці практичних методів проведення високоякісної психічно-мовної підготовки майбутніх лікарів. Творчий потенціал майбутнього лікаря – це інтегративна якість, що відображає ступінь можливостей актуалізації основних творчих сил особистості в реальній практиці.
Mentally-speech component of creative self-development of future doctors
Harmonic combination of humanitarian preparation of future specialists with their professional formation is one of problems of medical education. Conceptual principles of development of pedagogical education of Ukraine perceive the content of socially-humanitarian preparation in intensification and professionalization of lingual, philosophical, political science, cultural science, sociological, physical culture and sanative education, etc. Creation of creative educational space provides development of creative potential of a future doctor by means of introduction of non-standard methods of educational activity, organization of searching and exploratory activities, promotion of initiative for searching own goals, etc. Purpose of the article is to characterize mentally-speech component of creative potential of future doctors and to define criteria, indicators and levels of its formation. It is necessary to pay attention on expansion of medical outlook, formation of professional consciousness of future doctors, on strengthening of direction on self-development of students’ personality, that promotes their self-realization and professional self-detection in professional preparation of specialists (including future doctors). Professional preparation of future doctors is a continued process of their formation not only as specialists, but as personalities. The article considers problems of formation of clinical thinking as basis of competency-oriented skills and abilities of future doctors, which can be solved with the help of innovative educational technologies, which provide application of methods of formation of creative and system thinking, designed not only reproduce received tasks, but to solve non-standard ones. We perceive prospects of further investigations in development of practical methods of conduction of high-qualitative and fascinating mentally-speech preparation of future doctors. The creative potential of the future doctor is an integrative quality that reflects the extent of the possibilities of actualizing the essential creative forces of the individual in a real transformative practice.
Keywords: студент-медик, клінічне мислення, розвиток творчих здібностей, якісна освіта, професіоналізм, БДМУ; student-medic, clinical thinking, development of creative abilities, high-quality education, professionalism, BSMU